Needs analysis on Indonesian language learning materials about agriculture for foreign speakers - Defina Usmansyah; Yumna Rasyid; Sakura Ridwan (Journal of Education and Learning (EduLearn), 2019)
The aim of this research was to analyze the needs on integrative content-based Indonesian language learning materials about agriculture for foreign speakers A2 level. Research and development design was used employing the Dick and Carey’s model combined with Borg and Gall’s model, as well as the model of learning materials development proposed by Tomlinson, Brown, and Jolly and Bolitho. This research was conducted at Indonesian for foreign speakers, Bogor Agricultural University program  (BIPA IPB) on academic year 2015-2017. The procedure comprised: pre-study, students’ and teachers’ needs analysis on teaching materials at BIPA IPB. The findings indicated that the teaching materials about agriculture are not available yet at IPB. Besides, the needs on integrative content-based Indonesian language learning materials about agriculture for students at A2 level and the teachers were indicated high.